Local banking structure and firms’ performance: Evidence from Indonesia - Rosita Mei Damayanti; Putra Pamungkas (Jurnal Keuangan dan Perbankan, 2020)
This study investigates the relationship between financial development and firm’s performance. Our unique dataset allows us to identify different source of finance, whether it is from formal (commercial, rural, and sharia bank) or other sources. Using provincial and firms level data of 33 provinces in Indonesia over the period 2007-2013, we find that lending has a positive relationship on firm’s performance. The effect is different depending on the level of economic development and size of the firm. The lending from commercial and rural bank is positively correlated with the firm's performance in developed region. However, in less developed region, rural bank has a negative relationship on the firm’s performance. Lending from commercial, rural, and sharia bank positively linked with the performance of small, medium, and large firm’s performance. Improving and promoting lending to firms will accelerate firm’s performance. Firms might also take consideration to find the source of finance other than banks. JEL Classifications: G21, G32DOI: https://doi.org/10.26905/jkdp.v24i4.4800